The determination of the nursing students prevalance of cigarette smoking and affecting factors - Koç, Z.; Sağlam , Z. (Journal of Dependence, 2008)
Introduction: This is a descriptive study designed to investigate the prevalence of smoking among nursing students, the factors affecting smoking, the reasons for current smoking, and their approaches to quitting and not smoking. Method: The study was conducted on 128 nursing students, and data were collected using a 28-question survey in March 2005. Findings: The prevalence of smoking was found to be 28.1%. One in four nursing students included in the study was found to be a smoker. It was determined that 88% of non-smoking nursing students did not smoke for health reasons. It was determined that nursing students continued to smoke due to stress (63.9%). The educational level of the nursing students’ mothers and fathers was associated with an increase in smoking prevalence (p<0.05). Friendships (61.1%) were also determined to be risk factors for smoking status (p<0.01). Furthermore, family type and marital status were not determined to be risk factors for smoking status (p>0.05). Conclusion: The data obtained in our study were compared and evaluated with the results of other studies, and various recommendations were offered to prevent smoking. Based on these results, it can be concluded that nursing students are aware of the negative effects of smoking, but they are unable to apply this knowledge to their daily lives.